2019
DOI: 10.1002/cpt.1377
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity and Cardiovascular Risks Related to Allopurinol and Febuxostat Therapy in Asians: A Population‐Based Cohort Study and Meta‐Analysis

Abstract: The safety of newer xanthine oxidase inhibitor febuxostat compared to allopurinol remains unclear. To compare the risks of allopurinol hypersensitivity and febuxostat hypersensitivity and cardiovascular diseases (CVDs) in Asians, we conducted a population‐based cohort study enrolling patients receiving allopurinol or febuxostat from Chang Gung Memorial Hospital Health System across Taiwan during 2012–2016 and further performed a meta‐analysis incorporating two recent studies. Among the 61,539 users, a correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…Although less associated with hypersensitivity, one particular concern with febuxostat is that increased CV mortality has been observed in patients with underlying CV disease . However, a recent study has found no significant difference in CV deaths for febuxostat users and allopurinol users, which is consistent with our results . As described, our cohort differs drastically from the former study, which consists only of patients with CV disease, necessitating further research on febuxostat's association with CV death in our target population of patients with stage 5 CKD with or without comorbid CV disease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although less associated with hypersensitivity, one particular concern with febuxostat is that increased CV mortality has been observed in patients with underlying CV disease . However, a recent study has found no significant difference in CV deaths for febuxostat users and allopurinol users, which is consistent with our results . As described, our cohort differs drastically from the former study, which consists only of patients with CV disease, necessitating further research on febuxostat's association with CV death in our target population of patients with stage 5 CKD with or without comorbid CV disease.…”
Section: Discussionsupporting
confidence: 87%
“…However, recent study results have not reached a consensus regarding the mortality risk of febuxostat and allopurinol. Higher risk of cardiovascular (CV) death and all‐cause mortality for febuxostat users suggested by one RCT has not been demonstrated in other cohort studies . To our knowledge, large‐scale studies investigating febuxostat's renoprotective potential and mortality risk in patients with predialysis stage 5 CKD are lacking.…”
mentioning
confidence: 94%
“…Furthermore, the CARES trial showed internal inconsistency between primary MACE and CVD mortality end points, whereas FAST findings were internally consistent. Finally, results of several recent large-scale pharmacoepidemiologic studies also support the findings of the FAST study but not the CARES trial (9)(10)(11).…”
Section: Implications Of the Fast Findings Together With Cares Trial Datasupporting
confidence: 62%
“…An increasing number of clinical studies show that allopurinol can improve cardiovascular outcomes in patients with heart failure (HF), CHD, type 2 diabetes (T2D), and left ventricular hypertrophy (LVH) (Doehner et al, 2002;Farquharson et al, 2002;George et al, 2006;Noman et al, 2010;Rekhraj et al, 2013;Szwejkowski et al, 2013). Compared to allopurinol, whether febuxostat improves cardiovascular outcomes remains controversial (White et al, 2018;Zhang et al, 2018;Chen et al, 2019). Furthermore, whether UAlowering treatment (ULT) is beneficial to patients with asymptomatic hyperuricemia is uncertain because these patients are often associated with a variety of risk factors (such as old age, chronic kidney disease, cardiovascular disease, obesity, metabolic syndrome, alcohol, or smoking habits, etc.)…”
Section: Introductionmentioning
confidence: 99%